Prosody and sentence processing in Brazilian Portuguese: a Visual World Paradigm study - Caldas, Vitor Gabriel (Revista da ABRALIN, 2024)
This paper explores the role of prosody in the processing of garden-path sentences in Brazilian Portuguese. The structure investigated presents a dicendi (‘saying’) matrix verb with two that-clauses (A alunai disse à professoraj que –j estava atrasada que –i precisaria sair da sala - ‘The student told the teacher that was late that she would need to leave the room’). The first that-clause is temporarily ambiguous between a Complement Phrase (CP) and a Relative Clause (RC) analysis. We assume that different prosodic phrasing patterns will be aligned with different syntactic analyses, guiding listeners to parse the ambiguous clause either as CP or as an RC. A Visual World Paradigm study, using an eye-tracking equipment, was carried out to assess participants’ processing and comprehension of the ambiguity. 32 undergraduate students listened to sentences, with either a Garden-Path (GP) prosody or a No Garden-Path (NGP) prosody, and visualized two pictures representing the CP and the RC analyses of the ambiguous clause on a computer screen while an eye-tracker monitored their eye movements. The results showed that, when participants listened to a CP prosody, there were more fixations at the CP pictures. When they listened to an RC prosody, there were more fixations at the RC pictures. Also, there was a higher percentage of errors to a comprehension question when participants were exposed to the GP prosody conditions, indicating a higher level of difficulty.